Striking a new balance? US-China relations under Trump - Andreas Bøje Forsby (Danish Institute for International Studies (DIIS), 2017)
This report, commissioned by the Danish Ministry of Defense, examines the current state of US-China relations following Donald Trump's surprise win in the US presidential elections. Given Trump's harsh China-bashing rhetoric during his campaign, a complete meltdown of US-China relations appeared to be a likely scenario once Trump took over the Oval Office. After a rocky start, however, the first summit between Xi and Trump in April in Mar-a-Lago has seemingly been instrumental in putting bilateral relations back on track, with the two leaders agreeing to continue, in a somewhat altered form, the Obama administration's institutionalized US-China dialogue on how to jointly manage a wide range of difficult bilateral issues, including the highly unbalanced trade relationship. Furthermore, apart from its decision to accelerate deployment of the THAAD missile defense system to South Korea in the face of strong Chinese protests, the Trump administration has so far shied away from directly challenging any of China's key interests. Even the South China Sea - one of the central arenas of geopolitical rivalry between Washington and Beijing during the Obama administration - has been remarkably calm, primarily because China has adopted a relatively low profile after several years of maritime assertiveness in these highly contested waters. Yet, despite recent development trends, this report argues that US-China relations remain highly unstable, with the prospect of great power rivalry constantly looming on the horizon. In fact, evidence of an emerging US-China great power rivalry has been piling up over the past decade, fueled by what we may refer to as a set of underlying structural drivers. These include power and security dynamics, zero-sum economic competition and incompatible identity-generated grand strategies that, taken together, tend to erode mutual trust and cooperation between China and the United States. For instance, although currently calm, the report points out why strategic rivalry is likely soon again to stir up the waters of the South China Sea, as Beijing's assertive claims to "historic rights" in the sea clash with Washington's objective to orchestrate a maritime order in the region. Trump's decision in late May to resume the US Freedom of Navigation Operations program in the South China Sea points in this direction. Adding further to the vulnerability of bilateral relations is the report's finding that Beijing and Washington are no longer tied together on the international stage by a set of strong, shared interests that motivate them to set aside more deep-seated differences. Specifically, the international struggle against climate change offers the most prominent example of an ambitious joint US-Chinese agenda that has now been scrapped by the Trump administration. Currently, their joint efforts to curb North Korea's controversial nuclear weapons program - as witnessed most recently in early June with the adoption of UN Security Council Resolution 2356 - seem to be the only example of a strong, shared interest between Beijing and Washington. However, Trump's inclination to press ahead with THAAD and to "exert maximum pressure" in dealing with the North Korean regime could undermine US-Chinese cooperation on the Korean Peninsula. More generally, it could be argued that Beijing and Washington share an overall commitment to maintaining international order and stability, but that may not easily translate into substantive cooperative measures as long as their perspectives and outlooks differ so fundamentally. Against this backdrop, the report concludes that the overall relationship between China and the United States resembles that of rivals far more than partners. While the emerging great power rivalry will be kept at bay only as long as Donald Trump and Xi Jinping find it expedient to actively pursue a cooperative relationship - or insofar as their foreign policy agendas are eclipsed by domestic concerns - their priorities could easily change. Having officially abandoned Obama's "Rebalance to Asia", the Trump administration has yet to formulate a new coherent (i.e. grand) strategy for its engagement in Asia in general and its relationship with China in particular. In any case, striking a new strategic balance, whereby Beijing is designated as a partner rather than rival, appears unlikely given the underlying conflicts of interest.
Keywords: 300